2D CoP supported 0D WO3 constructed S-scheme for efficient photocatalytic hydrogen evolution. (17th June 2021) - Li, Teng; Guo, Xin; Zhang, Lijun; Yan, Teng; Jin, Zhiliang
Abstract: For heterojunction composite photocatalyst, intimate contact interface is the key to the carrier transfer separation conditions. Due to the interface contact, the electron transfer rate between catalysts can be increased during photocatalytic hydrogen production, therefore, we design the close contact of 0D/2D heterojunction, which greatly enhanced the photocatalytic hydrogen production activity of the composite catalyst. The composite catalyst WO3 /CoP was obtained by simple high temperature in situ synthesis. Moreover, it was proved by photoelectric chemistry and fluorescence tests that appropriate conduction band and valence band locations of WO3 and CoP provided a favorable way for thermodynamic electron transfer. In addition, fluorescence results showed that WO3 load effectively promoted photoelectron-hole transfer and increased electron lifetime. The formation of S-scheme heterojunctions can make more efficient use of useful photogenerated electrons and prevent the photogenerated electron-hole recombination of CoP itself, further promote the liveness of photocatalytic H2 evolution. Meanwhile, the study of Metal-organic frameworks (MOFs) materials further promoted the application of MOFs derivatives in the field of photocatalytic hydrogen evolution, and provided a reference for the rational design of composite catalysts for transition metal phosphide photocatalysts. Highlights: Composite catalyst WO3 /CoP was synthesized by a simple high temperature in situ method. An S-scheme heterojunction composed of CoP and WO3 was formed. The recombination of photoinduced electron-hole pairs was inhibited.